2013
DOI: 10.1680/macr.12.00211
|View full text |Cite
|
Sign up to set email alerts
|

Axial capacity and ductility of circular UHPC-filled steel tube columns

Abstract: This paper presents an experimental study of circular ultra-high-performance concrete-filled steel tube (UHPCFT) columns under monotonic axial compression. Some performance indices, termed concrete contribution ratio (CCR), strength enhancement index (SI) and ductility index (DI), are investigated in relation to the diameter-to-thickness ratio (D/t ) of the UHPCFT columns. The axial bearing capacities of the UHPCFT columns obtained from the test results are compared with Eurocode 4, American Concrete Institute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(21 citation statements)
references
References 7 publications
0
20
0
1
Order By: Relevance
“…[8], and Redaelli et al [9]. As an alternative to conventional steel reinforcement, researchers have also studied the potential of using cast-in-place FRP and steel tubes to enhance the axial performance of UHPFRC columns [10,11]. The research related to short UHPFRC columns reinforced with conventional reinforcement is summarized in the section that follows.…”
Section: Previous Research On Compressive Behavior Of Uhpfrcmentioning
confidence: 99%
“…[8], and Redaelli et al [9]. As an alternative to conventional steel reinforcement, researchers have also studied the potential of using cast-in-place FRP and steel tubes to enhance the axial performance of UHPFRC columns [10,11]. The research related to short UHPFRC columns reinforced with conventional reinforcement is summarized in the section that follows.…”
Section: Previous Research On Compressive Behavior Of Uhpfrcmentioning
confidence: 99%
“…The same researchers at Istanbul Technical University, Turkey that compared the results of axial capacity of UHPC composite columns and compared it to EC4 also looked at the ACI code. They found that results are, on average, 20% lower in design compared to experimental results (27). The ACI design code is currently very conservative when estimating the axial capacity of UHPC filled steel tubes.…”
Section: American Concrete Institute (Aci)mentioning
confidence: 99%
“…Researchers at Istanbul Technical University, Turkey tested the axial capacity of UHPC filled steel tube and compared the results to the EC4 design procedure. It has been found that the EC4 overestimates the axial bearing capacity by about 15% because it includes the confinement effect of the tube (27). This is a rather aggressive estimation to the capacity of the column and needs a reduction factor.…”
Section: Eurocode 4 (Ec4)mentioning
confidence: 99%
“…Previous studies on UCFST members concentrated mainly on their monotonic behavior. Several concentric and eccentric axial compression tests have been conducted to investigate the effects of yield stress of steel, compressive strength of UHPC, steel tube diameter-to-thickness ratio and length-to-depth ratio on the behavior of UCFST columns (Guler et al, 2013; Liew and Xiong, 2010; Portolés et al, 2013). Accordingly, several design equations have been proposed to calculate the axial compressive strength of UCFST columns.…”
Section: Introductionmentioning
confidence: 99%